ANALYSIS OF DIGITAL-BASED BANKING SERVICES TOWARDS COMPETITIVE ADVANTAGE IN INDONESIAN SYARIAH BANK - WATI, ADE IRNA (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
Some of the advantages of Indonesian Sharia banks in running their businesses have prioritized application technology as the spearhead of service and marketing to potential customers. In addition, the use of application technology, or banking services have technically implemented digitalization. In addition, Indonesian Sharia Bank has various funding products that can be used by the public among the profit sharing systems which are superior products of Islamic banking. This research has been conducted to prove how the influence of digital-based Islamic banking innovation variables and customer trust on the competitive advantage of Islamic banking. For the population in this study, the researchers determined the Indonesian Sharia Bank Labuhanbatu Regency which was registered and registered in December 2022 which amounted to around 1,203 customers. For how the sampling works in this study, the researcher determines the minimum sample size in PLS-SEM, which is around 30-100 samples. Therefore, the authors in this study targeted 100 people to be sampled. This research produces information data that shows that digital-based Islamic banking innovation is not an important thing in achieving competitive advantage in Islamic banking but an important concept in Islamic business, namely the main trust of customers in Islamic banking. Trust is the most important thing to achieve competitive advantage in Islamic banking in facing competition with conventional banks.